Surface Structural Analysis of the Layered Perovskite Ca1.9Sr0.1RuO4 by Low Energy Electron Diffraction I-V - Ismail Ismail; Rongying Jin; David Mandrus; Earl Ward Plummer (Aceh International Journal of Science and Technology, 2018)
Abstract – The atomic structure at surface of the layered perovskite Ca1.9Sr0.1RuO4 has been studied by Low Energy Electron Diffraction (LEED) I-V. The perovskite Ca1.9Sr0.1RuO4 of single crystal was cleaved in ultra high vacuum chamber (the pressure in the chamber was about 1x10-10 Torr). The experiments were conducted at room temperature (T=300 K). The sharp LEED pattern was observed which indicates that the surface of Ca1.9Sr0.1RuO4 is flat and it is a well ordered crystal. LEED I-V data, nine equivalent beams of the layered perovskite Ca1.9Sr0.1RuO4 were recorded at room temperature. LEED I-V calculation was performed to fit experimental data to obtain the surface atomic structure. The LEED I-V analysis reveals that in the surface of the layered perovskite Ca1.9Sr0.1RuO4 the RuO6 octahedra are rotated (in-plane rotation) alternating clockwise and counterclockwise. The in-plane rotation at the surface is 11 degree which is smaller than that in the bulk (13 degree). The Ru – O(1) bond-length at the surface is found to be 1.936 Å which is about the same as in the bulk (1.939 Å). The Ru – O(2) bond length at the surface is 1.863 Å which is much shorter than that in the bulk (2.040 Å). The volume of octahedral Ru-O6 at the surface is reduced by 9% with respect to the bulk. This finding shows that the atomic structure at surface of the layered perovskite Ca1.9Sr0.1RuO4is significantly different than that in the bulk. These lattice distortions strongly influence its electronic properties.   Key words: Transition Metal Oxide; Perovskite; Surface Atomic Structure; LEED I-V